Identification of promising and stable genotypes of wheat (Triticum aestivum L.) for grain yield under varied climatic conditions of north-western Himalayas using joint regression analysis - Priyanka; Rana, Vijay; Basandrai, Daisy; Sood, V K; Rana, Amit (Journal of Cereal Research, 2024)
The present investigation was undertaken to determine the stability of wheat genotypes for grain yield under varied environmental conditions prevalent in north- western Himalayas. A total of 60 genotypes including four checks were evaluated during three cropping seasons (Rabi 2019-20 to 2021-22). The stability was estimated using Eberhart and Russell model for six traits viz., days to 50% flowering, days to 75% maturity, flag leaf area (cm2), tillers per plant, biological yield, and grain yield per plant. The pooled analysis of variance showed differential behavior of genotypes over the environments. The most stable genotypes identified for days to 50% flowering, days to 75% maturity, flag leaf area (cm2), tillers per plant, biological yield and grain yield per plant was HPW 474. However, the promising and stable genotypes identified specifically for grain yield were HPW 474, HPW 368 and HD 2967. Thus, the genotypes found stable and well adapted to all the types of environments could be exploited as elite gene pool in future breeding programme, where aim is to develop high yielding and stable genotypes over environments or could be further tested in multilocation trials to be released as a cultivar.